Strategies and Challenges of School Business Marketing: A Case Study of SMKN 3 Malang - Ramadhan, Arya Gumilang; Juharyanto; Rochmawati; Maulana, Wildhan Ichzha; Isnaini, Nurul Azizatul (Jurnal Manajemen, 2024)
Marketing management for business schools has become increasingly important in the face of growing competition. This article examines the marketing strategies and challenges faced by SMKN 3 Malang in managing and promoting the school’s hotel business. The primary focus of this research is to understand how marketing can be used as a tool to enhance the school’s independence through a sustainable business model. This study employs a qualitative method with a case study approach at SMKN 3 Malang. Data were collected through in-depth interviews with the school’s curriculum vice principal, business marketing manager, and business operations manager, as well as through document analysis and direct observation. The study found that SMKN 3 Malang utilizes various marketing strategies, both online and offline, to attract customers. Platforms like Traveloka and Agoda are used for online marketing, while brochures and neon boxes are utilized in offline marketing strategies. Challenges include fierce competition with other hotels, limited resources, and a lack of professional marketing staff. The article concludes that despite various challenges, effective marketing can play a crucial role in supporting the independence and sustainability of the school’s business